2012
DOI: 10.1111/j.1464-410x.2012.11237.x
|View full text |Cite
|
Sign up to set email alerts
|

Detecting internet activity for erectile dysfunction using search engine query data in the Republic of Ireland

Abstract: What's known on the subject? and What does the study add?Despite the increasing prevalence of erectile dysfunction (ED), there is reluctance among symptomatic patients to present to healthcare providers for appropriate advice and treatment.A number of Internet campaigns have been launched by the Irish healthcare media since 2007 aiming to provide easily accessible advice on ED. Novel online technologies appear to provide a useful tool for educating the general public on the symptoms of ED because there has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…On one hand, these data could be interpreted as the consequence of an increase in ED awareness among both patients and primary care physicians. Indeed, the widespread availability of PDE5Is and the potential impact of the internet and public media [25,26] may result in patients feeling less embarrassed to discuss and seek medical attention for their sexual issues and being more confident regarding the possibility of an effective treatment. Likewise, the availability of educational programs dedicated to the importance of ED as a widespread condition affecting men's quality of life, and eventually serving as a sentinel marker of major health conditions, could have prompted primary care physicians to investigate ED more comprehensively even in younger individuals and to refer certain patients for a second-level andrological assessment.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, these data could be interpreted as the consequence of an increase in ED awareness among both patients and primary care physicians. Indeed, the widespread availability of PDE5Is and the potential impact of the internet and public media [25,26] may result in patients feeling less embarrassed to discuss and seek medical attention for their sexual issues and being more confident regarding the possibility of an effective treatment. Likewise, the availability of educational programs dedicated to the importance of ED as a widespread condition affecting men's quality of life, and eventually serving as a sentinel marker of major health conditions, could have prompted primary care physicians to investigate ED more comprehensively even in younger individuals and to refer certain patients for a second-level andrological assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Swenson and Lindblom [21] analyzed Google Trends for “breast cancer,” “colon cancer,” and “cervical cancer” and reported that cancer awareness month campaigns, specifically breast cancer and colon cancer, increased public awareness as shown by increased Web search activities. In the Republic of Ireland, Davis et al [22] found a direct association between media campaigns for erectile dysfunction and related search activity patterns. Despite limited research on the influence of health campaigns on search activity, other studies showed that media events including news reports and announcements regarding public figures also prompted health seeking behaviors [22-24].…”
Section: Introductionmentioning
confidence: 99%
“…In the Republic of Ireland, Davis et al [22] found a direct association between media campaigns for erectile dysfunction and related search activity patterns. Despite limited research on the influence of health campaigns on search activity, other studies showed that media events including news reports and announcements regarding public figures also prompted health seeking behaviors [22-24]. These findings suggest potential value for assessing search activity trends; however, further research is needed in this area to evaluate the effectiveness of infoveillance for monitoring health campaigns.…”
Section: Introductionmentioning
confidence: 99%
“…Gunn III and Lester surveyed suicides using search engines [39], and other scholars have replicated these findings [40, 41], while Deluca and collaborators exploited the Web for studying the epidemiology of drug addiction [42]. Internet key-word searching has been used also in the field of human sexuality, trying to better understand the dating and mating behaviors [43, 44]. another interesting application of Web hit search is the real-time detection of kidney stone diseases [45], but so far, to our knowledge, no one has explored the possibility of monitoring Google searches that refer to MS and associated concepts.…”
Section: Introductionmentioning
confidence: 99%